2017
DOI: 10.2147/dddt.s144415
|View full text |Cite
|
Sign up to set email alerts
|

10<em>H</em>-3,6-Diazaphenothiazine induces G<sub>2</sub>/M phase cell cycle arrest and caspase-dependent apoptosis and inhibits cell invasion of A2780 ovarian carcinoma cells through the regulation of NF-&kappa;B and (BIRC6-XIAP) complexes

Abstract: The asymptomatic properties and high treatment resistance of ovarian cancer result in poor treatment outcomes and high mortality rates. Although the fundamental chemotherapy provides promising anticancer activities, it is associated with severe side effects. The derivative of phenothiazine, namely, 10H-3,6-diazaphenothiazine (PTZ), was synthesized and reported with ideal anticancer effects in a previous paper. In this study, detailed anticancer properties of PTZ was examined on A2780 ovarian cancer cells by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…X-chromosome-linked IAP (XIAP), one of the eight human IAP proteins, has been found to exert the most pronounced antiapoptotic function, which is associated with its ability to block caspase−3, −7, and −9 (61). Moreover, some studies have demonstrated that XIAP has also been implicated in the regulation of NF-κB (62). In a previous study, it was found that -Ru1 induces apoptosis through the mitochondrial-mediated pathway, and regulates the expression of proapoptotic proteins, including the downregulation of Bcl-2/Bcl-xl, and the up-regulation of cytochrome c (Cyt C), caspase 9 and caspase 3 (32).…”
Section: Discussionmentioning
confidence: 99%
“…X-chromosome-linked IAP (XIAP), one of the eight human IAP proteins, has been found to exert the most pronounced antiapoptotic function, which is associated with its ability to block caspase−3, −7, and −9 (61). Moreover, some studies have demonstrated that XIAP has also been implicated in the regulation of NF-κB (62). In a previous study, it was found that -Ru1 induces apoptosis through the mitochondrial-mediated pathway, and regulates the expression of proapoptotic proteins, including the downregulation of Bcl-2/Bcl-xl, and the up-regulation of cytochrome c (Cyt C), caspase 9 and caspase 3 (32).…”
Section: Discussionmentioning
confidence: 99%
“…The tested compound for present study, namely PTZ was the tested compound preceded from previous studies. [19] Phenothiazine derivative was synthesized by professional medicinal chemistry research group from Medical University of Silesia, Sosnowiec, Republic of Poland; and this compound was synthesized according to the information obtained from respective publications. The detailed characteristic of this compound was explained in respective reports.…”
Section: Tested Compoundmentioning
confidence: 99%
“…[15][16][17] Beyond the routine metabolic functions of estrogen hormone, binding of the estrogen to its membrane-bound receptors (ESR1 and ESR2) tends to produce several downstream targeted genes, which are generally involved in regulation of cell division and proliferation, inhibit cell death mechanism, and promote secondary metastasis of cancer cells. [18][19][20] It is commonly known that dietary factors such as high glucose diet intake would increase the risk to have breast cancer. [21] In cellular biology, the AKT1 gene detected presence of high glucose molecules and send the signals to pancreas for secretion of insulin hormone for glycolysis process; despite high amount of insulin eventually promoting cells to synthesize more insulin-like growth factor-1 receptor (IGF-1R) on surface of plasma membrane for cellular intake of glucose and subsequent glycolysis process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations